2010
DOI: 10.1166/jnn.2010.2295
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversion of 1,2-Dichlorobenzene Over Mesoporous Materials from Zeolite

Abstract: In this study, 1,2-dichlorobenzene (DCB), an important precursor of PCDDs and PCDFs, was chosen as a suitable model compound for the catalyzed deep oxidation of dioxin. The recently developed mesoporous materials from zeolites (MMZ) were used for the first time as a support for an oxidation catalyst. The catalytic oxidation of 1,2-dichlorobenzene over Pt/MMZ was carried out, and the catalytic activity was compared with that of Pt/gamma-Al2O3, Pt/Al-MCM-41 and Pt/Beta catalysts. Pt/MMZ showed the highest cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Then, its pH was adjusted to 10 using 50 wt.% acetic acid, and the solution again reacted for another 48 h. The pH adjusting process was repeated three times. The solution was then washed with distilled water, filtered, and dried in the oven for 24 h. This was followed by another washing with ethanol and filtering, and again dried for 24 h and baked at 550°C for 4 h. Aluminum incorporation into MCM-48 was performed using the post-synthetic grafting method [16]. Before baking, the prepared MCM-48 was introduced into a solution prepared by dissolving AlCl 3 in 100 mL of ethanol, according to the desired Si/Al ratio, and then stirred for 24 h, washed with ethanol, filtered, dried for 24 h, and calcined for 4 h at 550°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, its pH was adjusted to 10 using 50 wt.% acetic acid, and the solution again reacted for another 48 h. The pH adjusting process was repeated three times. The solution was then washed with distilled water, filtered, and dried in the oven for 24 h. This was followed by another washing with ethanol and filtering, and again dried for 24 h and baked at 550°C for 4 h. Aluminum incorporation into MCM-48 was performed using the post-synthetic grafting method [16]. Before baking, the prepared MCM-48 was introduced into a solution prepared by dissolving AlCl 3 in 100 mL of ethanol, according to the desired Si/Al ratio, and then stirred for 24 h, washed with ethanol, filtered, dried for 24 h, and calcined for 4 h at 550°C.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the highly acidic catalyst would be better due to its high cracking ability. It has been reported that the catalytic activity of zeolites in cracking of hydrocarbons or biomass is correlated with their acidity [16-20]. In both terms of pore size and acidity, the more recently developed hierarchical meso-MFI zeolites (Meso-MFI) are suggested to apply for the catalytic pyrolysis of biomass due to its characteristics of high acidity and nanopore size [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Since their initial preparation in 1992, mesoporous silica materials have been applied to many fields. Mesoporous silica materials, such as MCM-41 and SBA-15, have large surface areas and homogeneous pore sizes [5][6][7][8][9][10]. In addition, the surface of mesoporous silica materials can be readily modified with organic groups to change their characteristics and achieve specific purposes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A TEM image is presented in Figure 5 to determine whether MMZZSM-5 and NiO/MMZZSM-5 have hexagonal structures. MMZZSM-5 has a well-ordered structure with mesopores that are hexagonal 1-D channels [31]. The NiO/MMZZSM-5 sample maintained the structural features of MMZZSM-5 after the nickel loading.…”
Section: Textural Properties Of Catalystsmentioning
confidence: 91%